2018
DOI: 10.13057/biodiv/d190418
|View full text |Cite
|
Sign up to set email alerts
|

Identification of active compounds and antifungal activity of Toona sinensis leaves fractions against wood rot fungi

Abstract: Elfirta RR, Falah S, Andrianto D, Lastini T. 2018. Identification of active compounds and antifungal activity of Toona sinensisleaves fractions against wood rot fungi. Biodiversitas 19: 1313-1318. Inhibitory activities of surian or toon (Toona sinensis) leavesfraction origin Sumedang, West Java, Indonesia against wood rot fungi (Ganoderma boninense IPBCC 10.658, Trametes versicolorInaCC F200, and Phanerochaete chrysosporium IPBCC 93.259) were studied. The samples were macerated using methanol andacetone. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…Meanwhile, in semipolar -polar extract of fraction DCM/MeOH (9/1) has more bioactive compounds such as sterol, phenol, flavonoid, and alkaloid (Widyawati, 2014). In Semipolarpolar extract of DCM/MeOH (9/1) may also have polar properties such as alkaloid, phenolic, saponin, carotenoid, tannin, amino acid, and glycoside (Elfirta, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in semipolar -polar extract of fraction DCM/MeOH (9/1) has more bioactive compounds such as sterol, phenol, flavonoid, and alkaloid (Widyawati, 2014). In Semipolarpolar extract of DCM/MeOH (9/1) may also have polar properties such as alkaloid, phenolic, saponin, carotenoid, tannin, amino acid, and glycoside (Elfirta, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…de Rodríguez et al (2017) stated that the mechanism of phenols against fungal pathogens is related with enzymatic inhibition through its oxidation. The presence of hydroxyl groups in phenolic compounds could link with sulphydryl groups in fungal proteins, changing the protein conformation of the cell wall (Elfirta et al, 2018).…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…Wang et al (2016) demonstrated that caffeine destroys the fungal protective layers (cell wall and cell membrane) and subcellular organelles. Also, a synergistic or complementary effect between phenolic compounds may occur, so that the effect of these interactions could be very useful in the fight against pathogens (de Rodríguez et al, 2017;Elfirta et al, 2018).…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…So far, tannins and amide were known to have antimicrobial activities against bacteria, fungi, and other pathogens (Shahat and Marzouk 2013). Tannin has hydroxyl groups and double bond α-β that were responsible for its antimicrobial properties (Elfirta et al 2018). The presence of tannins and amides in NCE (Figures 1 and 2) was expected as an antimicrobial agent that can be used in bioplastics.…”
Section: Antimicrobial Analysis Of Nc and Ncementioning
confidence: 99%